Dominant genera of plant-parasitic nematodes in kepok banana (Musa acuminata x balbisiana) cultivation in Pidie, Indonesia: English - Nasution, Siti Shofiya; Chamzurni, Tjut; Fitria, Cut; Izzati, Raichan (Jurnal Ilmiah Pertanian, 2025)
Banana (Musa spp.) is a vital agricultural commodity in Indonesia. In Pidie Regency, Aceh, Indonesia, production declined significantly by 46% between 2021 and 2023, partly due to infestations by plant-parasitic nematodes. This study aimed to identify the dominant genera of parasitic nematodes in the kepok banana (Musa acuminata × balbisiana) cultivar grown in Padang Tiji District, Pidie, Indonesia, using soil samples collected from three villages. Four nematode genera were identified: Pratylenchus, Helicotylenchus, Meloidogyne, and Xiphinema. Pratylenchus was dominant in Tunong Tanjong and Keupula Tanjong fields, while Helicotylenchus predominated in Tuha Peudaya. The highest nematode abundance was recorded in the Tunong Tanjong field, averaging 33,973.4 individuals per 10 g of soil. These findings provide valuable baseline data for nematode pest management and support the development of targeted control strategies to enhance sustainable banana cultivation in the region.